Contractile forces direct the chiral swirling of minimal cell collectives - Ghina Badih; Alexandre Schaeffer; Benoît Vianay; Pauline Smilovici; Laurent Blanchoin; Manuel Théry; Laëtitia Kurzawa (Proceedings of the National Academy of Sciences, 2025)
Chirality is a conserved biological feature with critical implications in tissue morphogenesis and embryonic development. In culture, multicellular groups exhibit spontaneous chiral symmetry break when moving collectively on micropatterned surfaces. Although several studies have shown that actin network integrity and actomyosin network contractility contribute to the establishment of the chirality of the movement, the role of contractile forces to the directionality of the chiral bias in collectives remains to be elucidated. Here, we studied the contractile forces produced by a minimal collective constituted of a pair of endothelial cells. We first show that cell doublets confined on disk-shaped micropatterns undergo spontaneous and persistent chiral swirling, displaying a mild but robust clockwise bias, as the one observed in bigger collectives. This bias could be amplified or reversed by modulating contractile forces. Traction force measurements revealed that high forces tend to drive counterclockwise rotation whereas low forces rather favor a clockwise rotation. Furthermore, the study of heterotypic doublets indicates that the direction of the rotation is determined by the more contractile cells within the doublets. These results thus revealed that contractile leader cells could drive the chiral motion of minimal collectives.